A CRITICAL STUDY ON COST ESCALATION IN CONSTRUCTION INDUSTRY - Kanchana, S.; Sukumaran, Anumol (International Journal of Engineering Technologies and Management Research, 2018)
Cost escalation refers to the changes occurring in cost of specific materials services in a given economy over a period of time. Construction industry is a most complicated and dynamic industry which is constantly facing uncertainties. The various factors that cause escalation in construction industry are studied and discussed in the article. The ideas suggested by researches were also analyzed and reported cost escalation can be minimized to a greater extent by carefully adopting the remedial measure.